2019
DOI: 10.1371/journal.pone.0217206
|View full text |Cite
|
Sign up to set email alerts
|

Assessing systemic and non-systemic transmission risk of tick-borne encephalitis virus in Hungary

Abstract: Estimating the tick-borne encephalitis (TBE) infection risk under substantial uncertainties of the vector abundance, environmental condition and human-tick interaction is important for evidence-informed public health intervention strategies. Estimating this risk is computationally challenging since the data we observe, i.e., the human incidence of TBE, is only the final outcome of the tick-host transmission and tick-human contact processes. The challenge also increases since the complex TBE virus (TBEV) transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 55 publications
(57 reference statements)
2
14
0
Order By: Relevance
“…The parameterized model was then used to conduct a retroactive assessment of the TBEV transmission patterns in the tick-host enzootic cycle in Hungary to conclude that the prevalence of TBEV transmission in the enzootic cycle had been increasing along with the observed warming weather. This study also confirmed that non-systemic (co-feeding) transmission, whereby a susceptible (larva or nymph) can acquire infection from co-feeding with infected nymphs in the same host even when the infection has not been established in the host [4], has been playing a very significant role in maintaining the transmission cycle of TBEV in Hungary and nearby regions [3,5,6]. Similar observations were made using a few early mechanistic models which incorporated the non-systemic transmission route [7][8][9].…”
supporting
confidence: 74%
See 3 more Smart Citations
“…The parameterized model was then used to conduct a retroactive assessment of the TBEV transmission patterns in the tick-host enzootic cycle in Hungary to conclude that the prevalence of TBEV transmission in the enzootic cycle had been increasing along with the observed warming weather. This study also confirmed that non-systemic (co-feeding) transmission, whereby a susceptible (larva or nymph) can acquire infection from co-feeding with infected nymphs in the same host even when the infection has not been established in the host [4], has been playing a very significant role in maintaining the transmission cycle of TBEV in Hungary and nearby regions [3,5,6]. Similar observations were made using a few early mechanistic models which incorporated the non-systemic transmission route [7][8][9].…”
supporting
confidence: 74%
“…A few laboratory experiments studied relationships between saturation deficit and some factors related to tick activities such as the duration of feeding and the quiescence [23]. These functional relationships could not be directly translated into the parameters of our model, however, in our previous study [3], several observation data were used to validate the parameterized model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a scenario was indeed proposed by Randolph and Rogers in their theory of the effects of climate change on the epidemiology of TBE [18]. Interestingly, the incidence of TBE in Hungary has also strongly declined since 1996 and the trend appears to continue at least until 2015 [33,34]. This country is adjacent to the eastern border of Austria and the Burgenland and has a similar Pannonian climate that differs substantially from the alpine regions of Austria and Switzerland where an upsurge of TBE was recorded [19,35].…”
Section: Discussionmentioning
confidence: 73%